PREDICTION OF GROUNDWATER STORAGE IN CISADANE WATERSHED - Dimas Ardi Prasetya; Roh Santoso Budi Waspodo; Satyanto Krido Saptomo (Departemen Teknik Sipil dan Lingkungan, IPB University, 2016)
Water is very important for human beings.Sources of fresh water that can be used are only 3% of the total water availability on earth, and 12% from that quantity are soureces of groundwater. Groundwater is one of the water resources that very important in sufficient human needs, such as domestic, agriculture or industry. Geoelectric is one of methods for groundwater investigation. The purposes of this research are to identify litholgy of soil layer, thickness of aquifer position on research location, determining hydraulic soil conductivity value and predict the groundwater reserve potential in Cisadane Watershed. This research was conducted in several steps, such as collected data and analysis data. The processed data was the secondary geoelectrical data with schlumberger method. Calculation of groundwater storage using geoelectric and Darcy’s law. Aquifer thickness layer obtained from the average content aquifer layer on research location, so it can represents the thickness of the aquifer. From the calculation result obtained groundwater reserve prediction amounted to 2.46 m3/second for unconfined aquifer and 8.64 m3/second for confined aquifer.